The association of COVID-19 vaccine availability with mental health among adults in the United States - Shen, Chan; Rashiwala, Lucy; Wiener, R. Constance; Findley, Patricia A.; Wang, Hao; Sambamoorthi, Usha (Frontiers in Psychiatry, 2022)
Objective: To assess whether COVID-19 vaccine approval and availability was associated with reduction in the prevalence of depression and anxiety among adults in the United States. Methods: We adopted cross sectional and quasi-experimental design with mental health measurements before vaccine availability (June 2020, N = 68,009) and after vaccine availability (March 2021, N = 63,932) using data from Census Pulse Survey. Depression and anxiety were derived from PHQ-2 and GAD-2 questionnaires. We compared rates of depression and anxiety between June 2020 and March 2021. Unadjusted and adjusted analysis with replicate weights were conducted. Results: Depression prevalence was 25.0% in June 2020 and 24.6% in March 2021; anxiety prevalence was 31.7% in June 2020 and 30.0% in March 2021 in the sample. In adjusted analysis, there were no significant differences in likelihood of depression and anxiety between June 2020 and March 2021. Conclusion: Depression and anxiety were not significantly different between June 2020 and March 2021, which suggests that the pandemic effect continues to persist even with widespread availability of vaccines.